Komparasi Kinerja Bank Umum Syariah di Indonesia: Analisis Islamicity Performance Index (IPI) - Wartoyo; Amalia Habibah, Sabrina; Abdul Wadud Kasyful Anwar, Abdul Muiz; Nur Haida, Nur (Salam (Islamic Economics Journal), 2025)
This research aims to measure the performance of Indonesian sharia banks and Indonesian Muamalat Bank using the Islamic performance index method. This method does not only measure financial performance, but is a method that is able to reveal the materialistic and spiritual values that exist in Islamic banks. The method used in this research is a qualitative descriptive method with data collection techniques using documentation techniques in annual reports on the official websites of each bank. The research results of these five ratios show the same results for four indicators, namely profit sharing ratio, zakat performance index, Islamic income vs non-Islamic income and Islamic investment vs non-Islamic investment where Indonesian Sharia Bank and Indonesian Muamalat Bank have a very unsatisfactory rating. However, the equitable distribution ratio indicator for Bank Muamalat Indonesia has a very satisfactory predicate, while for Indonesian sharia banks it has an unsatisfactory predicate. Keywords: Financial Performance, Sharia Bank, Islamic Performance Index